(untitled) (Revista Argentina de Cirugía, 2022)
Hepatic resection is the only potential curative treatment for patients with liver malignant disease, even for primary and metastasic lesions. The possibility of achieving a curative resection is limited by the future liver remnant and posthepatectomy liver failure (PHLF) is the most feared and severe com- plication. The Associating Liver Partition and Portal Vein Ligation for Staged Hepatectomy (ALPPS) has been introduced in the latest year as a novel strategy to avoid PHLF and allow the resection in patients with locally advanced disease previously considered unresectable. This technique is based on the li- gation of the disease liver portal vein and the transection of the hepatic parenchyma. This deviates portal flow to the non-tumoralliver and avoids cross flow through the parenchyma, which maximizes the future liver remnantvolume increase. The best candidates for this surgery are those patients con- sidered unresectable because of the size or the quality of the FLR. Current evidence regarding ALPPS shows promising short-term results. However, it is difficult to analy- ze these results from the oncological point of view because of the variety of diseases, chemotherapy schemes and technique variations among different surgeons. ALPPS is a feasible and safe strategy in experienced hands, which should be taken into account asan option, in properly selected oncologic patients that have been previously evaluated in multidiscipli- nary oncologic teams. Long-term results are still missing in order to define more clearly which is the role of this new tech- nique.